Construction of microbial consortia for microbial degradation of complex compounds - Cao, Zhibei; Yan, Wenlong; Ding, Mingzhu; Yuan, Yingjin (Frontiers in Bioengineering and Biotechnology, 2022)
The increasingly complex synthetic environmental pollutants are prompting further research into bioremediation, which is the most economical and safest means of environmental restoration. From the current research, it is more favorable for microbial consortia to degrade complex compounds than single bacteria. Biodegradation of complex compounds requires multiple enzymes. Some environmental pollutants that require biodegradation are also located in complex environments. Microbial consortia could better address these issues. Microbial consortia are more adaptable and stable to the growth environment and can provide a suitable catalytic environment for each enzyme required by the biodegradation pathway. With the development of synthetic biology and gene editing tools, the artificial microbial consortia system can be designed to be more efficient, stable and robust. The researches on microbial consortia system are promising in the degradation of complex compounds. This paper reviews the current advances on the degradation of complex compounds by microbial consortia, including plastics, petroleum, antibiotics, azo dyes, and some pollutants present in sewage. It also discusses the strategies for constructing a stable and robust microbial consortium to degrade complex compounds. Hoping some support can be brined by this paper to those who research the degradation of complex compounds by microbial consortia.